2021
DOI: 10.3390/ijms222212567
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Analyses of HF-Passivated Magnesium Screws for Guided Bone Regeneration (GBR)

Abstract: Background: Magnesium (Mg) is one of the most promising materials for human use in surgery due to material characteristics such as its elastic modulus as well as its resorbable and regenerative properties. In this study, HF-coated and uncoated novel bioresorbable magnesium fixation screws for maxillofacial and dental surgical applications were investigated in vitro and in vivo to evaluate the biocompatibility of the HF coating. Methods: Mg alloy screws that had either undergone a surface treatment with hydrofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
2
14
0
Order By: Relevance
“…This assumption is based on the fact that is well known that an apatite layer is forming at the surface of the BGs that might prevent former pH value shifts [13]. This observation might thus be comparable with findings made after implantation of magnesium-based biomaterials [65]. Recent advances in the understanding of corrosion mechanisms have shown that magnesium's susceptibility to corrosion occurs despite the presence of an oxide layer.…”
Section: Discussionsupporting
confidence: 69%
“…This assumption is based on the fact that is well known that an apatite layer is forming at the surface of the BGs that might prevent former pH value shifts [13]. This observation might thus be comparable with findings made after implantation of magnesium-based biomaterials [65]. Recent advances in the understanding of corrosion mechanisms have shown that magnesium's susceptibility to corrosion occurs despite the presence of an oxide layer.…”
Section: Discussionsupporting
confidence: 69%
“…This assumption is based on the fact that is well known that an apatite layer forms at the surface of bioglass that can prevent pH shifts (14). This observation might thus be comparable with findings made after implantation of magnesium-based biomaterials (49). Recent advances in the understanding of corrosion mechanisms have shown that corrosion of magnesium continues despite the presence of an oxide layer.…”
Section: Discussionsupporting
confidence: 68%
“…3D), the peak attributed to the symmetrical stretching vibration of –COO −36 at 1432 cm −1 was weakened, and no peak was detected for the N–H bond. The wide peak at ∼1123 cm −1 was attributed to the overlap of asymmetric stretching vibration peaks of (PO 3 ) 2–22,33 and the C–O bond. 39 The P–O–P bond belonging to polyphosphate was clearly observed.…”
Section: Resultsmentioning
confidence: 99%
“…20 For example, magnesium, which is widely used, presents good biocompatibility and biodegradability. 21 Schroder et al 20 claimed that magnesium polyphosphate (MPP) can promote the differentiation of bone marrow mesenchymal stem cells in cartilage cell lines and accelerate cartilage regeneration. Mu ¨ller et al 22 prepared a viscous paste-like biological matrix using MPP and hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%